Pathological Significance and Prognostic Value of Surfactant Protein D in Cancer. - Mangogna, Alessandro; Belmonte, Beatrice; Agostinis, Chiara; Ricci, Giuseppe; Gulino, Alessandro; Ferrara, Ines; Zanconati, Fabrizio; Tripodo, Claudio; Romano, Federico; Kishore, Uday; Bulla, Roberta (Front Immunol, 2018)
Surfactant protein D (SP-D) is a pattern recognition molecule belonging to the Collectin (collagen-containing C-type lectin) family that has pulmonary as well as extra-pulmonary existence. In the lungs, it is a well-established opsonin that can agglutinate a range of microbes, and enhance their clearance phagocytosis and super-oxidative burst. It can interfere with allergen-IgE interaction and suppress basophil and mast cell activation. However, it is now becoming evident that SP-D is likely to be an innate immune surveillance molecule against tumor development. SP-D has been shown to induce apoptosis in sensitized eosinophils derived from allergic patients and a leukemic cell line p53 pathway. Recently, SP-D has been shown to suppress lung cancer progression interference with the epidermal growth factor signaling. In addition, a truncated form of recombinant human SP-D has been reported to induce apoptosis in pancreatic adenocarcinoma Fas-mediated pathway in a p53-independent manner. To further establish a correlation between SP-D presence/levels and normal and cancer tissues, we performed a bioinformatics analysis, using Oncomine dataset and the survival analysis platforms Kaplan-Meier plotter, to assess if SP-D can serve as a potential prognostic marker for human lung cancer, in addition to human gastric, breast, and ovarian cancers. We also analyzed immunohistochemically the presence of SP-D in normal and tumor human tissues. We conclude that (1) in the lung, gastric, and breast cancers, there is a lower expression of SP-D than normal tissues; (2) in ovarian cancer, there is a higher expression of SP-D than normal tissue; and (3) in lung cancer, the presence of SP-D could be associated with a favorable prognosis. On the contrary, at non-pulmonary sites such as gastric, breast, and ovarian cancers, the presence of SP-D could be associated with unfavorable prognosis. Correlation between the levels of SP-D and overall survival requires further investigation. Our analysis involves a large number of dataset; therefore, any trend observed is reliable. Despite apparent complexity within the results, it is evident that cancer tissues that produce less levels of SP-D compared to their normal tissue counterparts are probably less susceptible to SP-D-mediated immune surveillance mechanisms infiltrating immune cells.

Complement Protein C1q Binds to Hyaluronic Acid in the Malignant Pleural Mesothelioma Microenvironment and Promotes Tumor Growth. - Agostinis, Chiara; Vidergar, Romana; Belmonte, Beatrice; Mangogna, Alessandro; Amadio, Leonardo; Geri, Pietro; Borelli, Violetta; Zanconati, Fabrizio; Tedesco, Francesco; Confalonieri, Marco; Tripodo, Claudio; Kishore, Uday; et al. (Front Immunol, 2017)
C1q is the first recognition subcomponent of the complement classical pathway, which acts toward the clearance of pathogens and apoptotic cells. C1q is also known to modulate a range of functions of immune and non-immune cells, and has been shown to be involved in placental development and sensorial synaptic pruning. We have recently shown that C1q can promote tumor by encouraging their adhesion, migration, and proliferation in addition to angiogenesis and metastasis. In this study, we have examined the role of human C1q in the microenvironment of malignant pleural mesothelioma (MPM), a rare form of cancer commonly associated with exposure to asbestos. We found that C1q was highly expressed in all MPM histotypes, particularly in epithelioid rather than in sarcomatoid histotype. C1q avidly bound high and low molecular weight hyaluronic acid (HA) its globular domain. C1q bound to HA was able to induce adhesion and proliferation of mesothelioma cells (MES) enhancement of ERK1/2, SAPK/JNK, and p38 phosphorylation; however, it did not activate the complement cascade. Consistent with the modular organization of the globular domain, we demonstrated that C1q may bind to HA through ghA module, whereas it may interact with human MES through the ghC. In conclusion, C1q highly expressed in MPM binds to HA and enhances the tumor growth promoting cell adhesion and proliferation. These data can help develop novel diagnostic markers and molecular targets for MPM.

C1q acts in the tumour microenvironment as a cancer-promoting factor independently of complement activation. - Bulla, Roberta; Tripodo, Claudio; Rami, Damiano; Ling, Guang Sheng; Agostinis, Chiara; Guarnotta, Carla; Zorzet, Sonia; Durigutto, Paolo; Botto, Marina; Tedesco, Francesco (Nat Commun, 2016)
Complement C1q is the activator of the classical pathway. However, it is now recognized that C1q can exert functions unrelated to complement activation. Here we show that C1q, but not C4, is expressed in the stroma and vascular endothelium of several human malignant tumours. Compared with wild-type (WT) or C3- or C5-deficient mice, C1q-deficient (C1qa(-/-)) mice bearing a syngeneic B16 melanoma exhibit a slower tumour growth and prolonged survival. This effect is not attributable to differences in the tumour-infiltrating immune cells. Tumours developing in WT mice display early deposition of C1q, higher vascular density and an increase in the number of lung metastases compared with C1qa(-/-) mice. Bone marrow (BM) chimeras between C1qa(-/-) and WT mice identify non-BM-derived cells as the main local source of C1q that can promote cancer cell adhesion, migration and proliferation. Together these findings support a role for locally synthesized C1q in promoting tumour growth.
Keywords: Animals; Apoptosis; Cell Line, Tumor; Cell Movement; Cell Proliferation; Complement Activation; Complement C1q; Complement C3; Complement C5; Humans; Mice; Mice, Inbred C57BL; Mice, Knockout; Neoplasms

Targeted tumor imaging of anti-CD20-polymeric nanoparticles developed for the diagnosis of B-cell malignancies. - Capolla, Sara; Garrovo, Chiara; Zorzet, Sonia; Lorenzon, Andrea; Rampazzo, Enrico; Spretz, Ruben; Pozzato, Gabriele; Núñez, Luis; Tripodo, Claudio; Macor, Paolo; Biffi, Stefania (Int J Nanomedicine, 2015)
The expectations of nanoparticle (NP)-based targeted drug delivery systems in cancer, when compared with convectional therapeutic methods, are greater efficacy and reduced drug side effects due to specific cellular-level interactions. However, there are conflicting literature reports on enhanced tumor accumulation of targeted NPs, which is essential for translating their applications as improved drug-delivery systems and contrast agents in cancer imaging. In this study, we characterized biodegradable NPs conjugated with an anti-CD20 antibody for in vivo imaging and drug delivery onto tumor cells. NPs' binding specificity mediated by anti-CD20 antibody was evaluated on MEC1 cells and chronic lymphocytic leukemia patients' cells. The whole-body distribution of untargeted NPs and anti-CD20 NPs were compared by time-domain optical imaging in a localized human/mouse model of B-cell malignancy. These studies provided evidence that NPs' functionalization by an anti-CD20 antibody improves tumor pharmacokinetic profiles in vivo after systemic administration and increases in vivo imaging of tumor mass compared to non-targeted NPs. Together, drug delivery and imaging probe represents a promising theranostics tool for targeting B-cell malignancies.

C1q as a unique player in angiogenesis with therapeutic implication in wound healing. - Bossi, Fleur; Tripodo, Claudio; Rizzi, Lucia; Bulla, Roberta; Agostinis, Chiara; Guarnotta, Carla; Munaut, Carine; Baldassarre, Gustavo; Papa, Giovanni; Zorzet, Sonia; Ghebrehiwet, Berhane; Ling, Guang Sheng; et al. (Proc Natl Acad Sci U S A, 2014)
We have previously shown that C1q is expressed on endothelial cells (ECs) of newly formed decidual tissue. Here we demonstrate that C1q is deposited in wound-healing skin in the absence of C4 and C3 and that C1q mRNA is locally expressed as revealed by real-time PCR and in situ hybridization. C1q was found to induce permeability of the EC monolayer, to stimulate EC proliferation and migration, and to promote tube formation and sprouting of new vessels in a rat aortic ring assay. Using a murine model of wound healing we observed that vessel formation was defective in C1qa(-/-) mice and was restored to normal after local application of C1q. The mean vessel density of wound-healing tissue and the healed wound area were significantly increased in C1q-treated rats. On the basis of these results we suggest that C1q may represent a valuable therapeutic agent that can be used to treat chronic ulcers or other pathological conditions in which angiogenesis is impaired, such as myocardial ischemia.
Keywords: Animals; Cell Proliferation; Complement C1q; DNA Primers; Endothelial Cells; Enzyme-Linked Immunosorbent Assay; Human Umbilical Vein Endothelial Cells; Humans; Immunoblotting; Immunohistochemistry; In Situ Hybridization; Mice; Mice, Inbred C57BL; Mice, Knockout; Neovascularization, Physiologic; Rats; Rats, Wistar; Real-Time Polymerase Chain Reaction; Wound Healing

Mesenchymal stem cells display hepato-protective activity in lymphoma bearing xenografts. - Secchiero, Paola; Corallini, Federica; Zavan, Barbara; Tripodo, Claudio; Vindigni, Vincenzo; Zauli, Giorgio (Invest New Drugs, 2012)
A disseminated model of non-Hodgkin's lymphoma with prevalent liver metastasis was generated by intraperitoneal (i.p.) injection of EBV(+) B lymphoblastoid SKW6.4 in nude-SCID mice. The survival of SKW6.4 xenografts (median survival = 27 days) was significantly improved when hyaluronan scaffolds embedded with mesenchimal stem cells (MSC) were implanted in the abdominal area 4 days after SKW6.4 injection (median survival = 39.5 days). Mice implanted with MSC showed a significant improvement of hepatic functionality in lymphoma xenografts, as demonstrated by measurement of serum ALT/AST levels. Co-culture of MSC with lymphoma cells enhanced the release of hepatocyte growth factor (HGF) by MSC. These data suggest that hyaluronan-embedded MSC exert anti-lymphoma activity by ameliorating hepatic functionality.
Keywords: Alanine Transaminase; Animals; Aspartate Aminotransferases; Biological Markers; Cell Communication; Cell Line, Tumor; Cell Survival; Coculture Techniques; Hepatocyte Growth Factor; Humans; Hyaluronic Acid; Liver; Liver Neoplasms; Lymphoma, Non-Hodgkin; Mesenchymal Stem Cell Transplantation; Mesenchymal Stromal Cells; Mice; Mice, Nude; Mice, SCID; Time Factors; Tissue Scaffolds; Xenograft Model Antitumor Assays

An alternative role of C1q in cell migration and tissue remodeling: contribution to trophoblast invasion and placental development. - Agostinis, Chiara; Bulla, Roberta; Tripodo, Claudio; Gismondi, Angela; Stabile, Helena; Bossi, Fleur; Guarnotta, Carla; Garlanda, Cecilia; De Seta, Francesco; Spessotto, Paola; Santoni, Angela; Ghebrehiwet, Berhane; et al. (J Immunol, 2010)
Fetal trophoblast cells invading the decidua in the early phase of pregnancy establish complex interaction with the maternal extracellular matrix. We discovered that C1q was widely distributed in human decidual stroma in the absence of C4 and C3 and was actively synthesized by migrating extravillous trophoblasts. The cells expressed the messages for the three chains of C1q and secreted this complement component that interacted with the proteins of the decidual extracellular matrix. Solid phase-bound C1q promoted trophoblast adhesion and migration, and cell binding to C1q resulted in activation of ERK1/2 MAPKs. Ab inhibition experiments showed that the receptors for the globular head of C1q/p33 and α(4)β(1) integrin were both involved in this process and were colocalized on the cell surface following binding of C1q to trophoblasts. We also found that C1q(-/-) mice manifested increased frequency of fetal resorption, reduced fetal weight, and smaller litter sizes compared with wild-type mice. C1q deficiency was associated with impaired labyrinth development and decidual vessel remodeling. Collectively, these data suggest that C1q plays an important role in promoting trophoblast invasion of decidua and that defective local production of C1q may be involved in pregnancy disorders, such as pre-eclampsia, characterized by poor trophoblast invasion.
Keywords: Animals; Cell Adhesion; Chemotaxis, Leukocyte; Complement C1q; Female; Humans; Immunoblotting; Immunohistochemistry; Immunoprecipitation; Mice; Mice, Inbred C57BL; Microscopy, Confocal; Placentation; Pre-Eclampsia; Pregnancy; Reverse Transcriptase Polymerase Chain Reaction; Trophoblasts